Medicinal plants and fungi : recent advances in research and development - Agrawal, Dinesh Chandra; Tsay, Hsin-Sheng; Shyur, Lie-Fen; Wu, Yang-Chang; Wang, Sheng-Yang, Ph. D. (Springer, 2017)
This book highlights the latest international research on different aspects of medicinal plants and fungi. Studies over the last decade have demonstrated that bioactive compounds isolated from medicinal fungi have promising antitumor, cardiovascular, immunomodulatory, anti-allergic, anti-diabetic, and hepatoprotective properties. In the light of these studies, the book includes chapters (mostly review articles) by eminent researchers from twelve countries across the globe working in different disciplines of medicinal plants and fungi. It discusses topics such as the prevention of major neurodegenerative and neurotoxic mechanisms by Centella asiatica; the medicinal properties and therapeutic applications of several mushrooms species found in different parts of the world; and fungal endophytes as a source of bioactive metabolites including anticancer and cardioprotective agents. There are also chapters on strategies for identifying bioactive secondary metabolites of fungal origin; the use of genomic information to explore the biotechnological potential of medicinal mushrooms; and solid state fermentation of agro-industrial and forestry residues for the production of medicinal mushrooms. It is a valuable resource for the researchers, professionals and students working in the area of medicinal plants and fungi.
Keywords: Medicinal plants.; Fungi -- Therapeutic use.; elektronické knihy; electronic books